RESPONSE OF SORGHUM (Sorghum bicolor L.) FODDER TO PHOSPHORUS FERTILIZER ON TORRIPSAMMENT SOIL. - M. Rashid; M. Iqbal (Journal of Animal and Plant Sciences, 2011)
Sorghum is an important fodder for animals in Pakistan. Phosphorus is a quality nutrient for fodders. The use of P for sorghum is negligible. Thus a field study was conducted to evaluate the effect of model based P fertilization to improve yield and quality of sorghum fodder on Torripsamment soil (Loamy sand, calcareous). Adsorption isotherm was constructed by equilibrating 2.5 g soil with 25 ml of 0.01 M CaCl2 solution containing 0, 20, 40, 60, 80, 100, 200,300,400 and 500 µg P mL-1 as KH2PO4 and shaking for 24 hour at 20 0C. P fertilizer doses were computed by using empirically derived Freundlich equation to adjust soil solution P levels of 0.05, 0.1, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, and 0.50 mg P L-1. It was observed that different P fertilizer doses were required to adjust different soil solution P levels. Adsorption of P increased with P application rate but marginal adsorption decreased significantly. Yield and quality of sorghum fodder were improved with P application. Yield increased upto T6 where P was applied @ 25 kg ha-1 but quality traits (P concentration, dry matter, crude protein, crude fiber and ash contents (%) improved with the highest rate of P use i.e. 43 kg ha-1. P application showed non-significant affect on NDF and ADF contents (%). External and internal P requirements of sorghum fodder to obtain 95 % relative yield were 0.22 mg L-1 and 0.20 % respectively.
Keywords: - P fertilization; derived Freundlich equation; sorghum yield and quality.